The Remarkable Diversity of Parasitic Flowering Plants in Colombia (2023)
ABSTRACT: Parasitic plants have evolved independently in 12 Angiosperm orders. Nine of them (Boraginales, Cucurbitales, Ericales, Lamiales, Laurales, Malvales, Santalales, Solanales, and Zygophyllales) are represented in Colombia by 17 families, 44 genera and 246 species, including facultative (37) and obligate (187) hemiparasites, holoexoparasites (19) and holoendoparasites (3). Cladocolea coriacea (Loranthaceae) is reported for the first time in Colombia. One genus (Sanguisuga, Cytinaceae) and 69 species (28.04%) are endemic to the country. Endemism decreases with elevation, ranging from 26 species (37.68%) below 1000 m, to one species (1.44%) above 4000 m. Speciation in Aetanthus, Psittacanthus and Tristerix (Loranthaceae), Dendrophthora and Phoradendron (Viscaceae), and Castilleja and Neobartsia (Orobanchaceae) was likely prompted by the Andean uplift. The highest number of species (169) are found in the Andean Region, whereas the Orinoco Region contains the lowest number (29). Dry forests and thickets, and coastal vegetation of the Caribbean Region are the preferred ecosystems for Krameria (Krameriaceae), Sanguisuga, Acanthosyris (Cervantesiaceae), Maracanthus (Loranthaceae), Ximenia (Ximeniaceae), Lennoa (Ehretiaceae), and Anisantherina (Orobanchaceae). Orobanche minor, recently introduced to the country, is the only potential weed for crops between 2500 and 3200 m in the Eastern Cordillera. Convergent lifeforms include: the obligate, twining stem holoparasitic Cassytha (Lauraceae) and Cuscuta (Convolvulaceae); the root holoexoparasitic Sanguisuga, Mitrastemon (Mitrastemonaceae), all Balanophoraceae, and Lennoa; and the root obligate hemiparasitic Krameria, Gaiadendron (Loranthaceae), and all Cervantesiaceae, Opiliaceae, Schoepfiaceae, Strombosiaceae and Ximeniaceae. Holoendoparasitism occurs only in Apodanthaceae, whereas root facultative hemiparasitism is restricted to the Orobanchaceae.